Hemodynamics of the superior mesenteric artery and splenic artery in healthy subjects and patients with portal hypertension: Investigatin with duplex Doppler ultrassonography - Derya SARAÇYAKUPOĞLU,; Ayşe ERDEN,; Tülay ÖLÇER,; Turhan CUMHUR, (Turkish Journal of Gastroenterology, 2019)
-